Taking back control of the energy sector? A legal analysis of Brexit and the EU-UK trade and cooperation agreement - GOLDBERG, Silke (University of Groningen Press, 2023)
This book focuses on the legal consequences of Brexit for the energy sector both in the United Kingdom and in the European Union. In particular, it considers to what extent the EU-UK Trade and Cooperation Agreement (TCA) is adequate for the energy sector post-Brexit by exploring whether the TCA delivers legal certainty, has been effectively implemented, and meets the Brexit objectives. The analysis of these questions leads to several recommendations, for instance in relation to the implementation of the TCA and its extension to new energy technologies.